Income inequality, tax base and sovereign spreads - Joshua Aizenman; Yothin Jinjarak (University of California, Economics Department, 2012)
This paper investigates the association between greater income inequality, de-facto fiscal space, and sovereign spreads. Using data from 50 countries in 2007, in 2009 and in 2011, we find that higher income inequality is associated with a lower tax base, lower de-facto fiscal space, and higher sovereign spreads. The economic magnitude of these effects is rather large: an increase in the Gini coefficient of inequality by 1 (in a scale of 0-100), is associated in 2011 with a lower tax base of 2 percent of the GDP, and with a higher sovereign spread of 45 basis points.
Keywords: H20; D63; F41; 330; income inequality; tax-base; fiscal space; sovereign spreads; Einkommensverteilung; Soziale Ungleichheit; Steuerbemessung; Öffentlicher Haushalt; Welt